Radiotherapy statements of the 18th St. Gallen International Breast Cancer Consensus Conference - a German expert perspective - Krug, David; Banys-Paluchowski, Maggie; Brucker, Sara; Denkert, Carsten; Ditsch, Nina; Fasching, Peter A.; Haidinger, Renate; Harbeck, Nadia; Heil, Jörg; Huober, Jens; Jackisch, Christian; Janni, Wolfgang; et al. (Strahlentherapie und Onkologie, 2024)
Purpose: To summarize the radiotherapy-relevant statements of the 18th St. Gallen Breast Cancer Consensus Conference and interpret the findings in light of German guideline recommendations. Methods: Statements and voting results from the 18th St. Gallen International Breast Cancer Consensus Conference were collected and analyzed according to their relevance for the radiation oncology community. The voting results were discussed in two hybrid meetings among the authors of this manuscript on March 18 and 19, 2023, in light of the German S3 guideline and the 2023 version of the Arbeitsgemeinschaft Gynäkologische Onkologie (AGO) guidelines. Results and conclusion: There was a high level of agreement between the radiotherapy-related statements of the 18th St. Gallen International Breast Cancer Consensus Conference and the German S3 and AGO guidelines. Discrepancies include the impact of number of lymph node metastases for the indication for postmastectomy radiotherapy.
Gesehen am 11.09.2024